The darkness outside us - Schrefer, Eliot, 1978- (Katherine Tegen Books, HarperCollins Publishers, 2021)
Earth's population is divided between only two existing countries which cannot manage to cooperate in any way, until a distress signal arrives from Titan's first settler. Neither country can afford to rescue her on their own if they act separately. Ambrose wakes up on board the Coordinated Endeavour under strange circumstances: he doesn't remember the launch, the ship's OS is voiced by his mother, strangers have been aboard, and Kodiak, the only other person on this mission, has barricaded himself away from sight. But nothing will stop Ambrose from making this mission succeed-- not when the settler he's rescuing is his sister.